Implementasi Program Ekspora: Upaya Peningkatan Self-Efficacy pada Siswa Kelas III SD - Keisya Damia Garbita; Frankly Juliston Pane; Rasya Kirana Putri Wibowo; Nadia Mutmainnah; M. Caesar Mumpuni; Annisa Dianesti Dewi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Low self-efficacy is one of the psychological challenges commonly found among elementary school students, characterized by lack of self-confidence in speaking, reluctance to participate actively, and avoidance of communication situations. This community service activity aimed to improve self-efficacy among third-grade students at SDN 091/IX Rengas Bandung Village, Muaro Jambi through the EKSPORA campaign program (Expression, Collaboration, Voice, Self-Confidence, and Action). The program was implemented in one day with four interconnected sessions: KENAL, BISA, PAHAM, and CAKAP, encompassing ice breaking, storytelling circles, paper relay activities, spontaneous description games, psychoeducation, FGD case studies, group presentations, and creative craft activities. A total of 18 third-grade students participated and were assessed using pre-test and post-test instruments. Results showed an increase in the average self-efficacy score from 2.28 to 2.67, with a total score difference of +7. Qualitatively, participants demonstrated positive behavioral changes including increased courage in speaking and growing initiative to participate actively in each session. This program contributes to achieving SDG 3 (Good Health and Well-being) and SDG 4 (Quality Education).